Echocardiographic calcification score in patients with low/intermediate cardiovascular risk - Hirschberg, Kristóf; Reinhart, Manuel; Mereles, Derliz; Uhlmann, Lorenz; André, Florian; Riffel, Johannes; Ochs, Marco; Katus, Hugo (Clinical research in cardiology, 2019)
PurposeCalcification of aortic valve and mitral annulus is associated with cardiovascular risk factors, morbidity and mortality. Assessment of cardiac calcification with echocardiography is feasible, however, only few structured scoring systems have been established so far with limited prognostic data. This study aimed to evaluate an echocardiographic calcification score (echo-CCS) in patients with low/intermediate cardiovascular risk.MethodsDigitally stored echocardiography studies of 151 patients (median age 64, 49.7% male) from February 2008 to December 2009 were retrospectively reviewed for calcifications of the aortic valve, aortic root, mitral annulus, papillary muscles and ventricular septum. A calcification score ranging from 0 to 5 was assigned to every patient and its relation to computed tomography calcium score, coronary stenosis and ESC SCORE was assessed. Follow-up data were collected from 149 patients (98.7%) with a median of 6.2 years. Logistic regression and Kaplan-Meier analysis were performed to assess the association of the echo-CCS with significant coronary artery disease (≥ 50% stenosis) and risk for cardiac events and all-cause mortality.ResultsAn association of the echo-CCS with the ESC SCORE (ρ = 0.5; p < 0.001) and a good correlation of the echo-CCS with the Agatston score (ρ = 0.73; p < 0.001) can be observed. Univariate regressions revealed that echo-CCS is a significant predictor for cardiac events [OR = 5.1 (CI: 1.7-15.0); p = 0.003], coronary intervention [OR = 2.8 (CI: 1.3-5.7); p = 0.006], hospitalisation for cardiac symptoms [OR = 2.0 (CI: 1.2-3.4); p = 0.007], all-cause mortality [OR = 2.6 (CI: 1.3-5.5); p = 0.01] and significant CAD [OR = 3.2 (CI: 1.9-5.4); p < 0.001].ConclusionsWe demonstrated the prevalence of an easily obtainable, radiation-free calcification score in patients with low/intermediate cardiovascular risk. The strong association with CT-calcium scoring may evoke its potential as an alternative method in CV risk assessment.
Published online: 6 August 2018
Gesehen am 24.10.2019